Dampak Sosial Ekonomi Pembangunan Gorontalo Outer Ring Road bagi Petani di Desa Talulobutu Selatan - Harold, Rudy; Wiroto, Dondick Wicaksono (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
Development of road infrastructure is one of the priorities of the Indonesian government to accelerate the recovery of Indonesia's economic conditions after the economic crisis that took place during the New Order government. This study aims to explore and analyze data and facts that will show various local social and economic issues in the farming community in the GORR construction site. This study uses a qualitative method. The results of this study indicate that In Gorontalo, the Gorontalo Outer Ring Road (GORR) road infrastructure development project is one of the government's strategies to improve the welfare of the people of Gorontalo. The construction of the ring road is intended to reduce traffic congestion (congestion), speed up the distribution of goods and people from the port to Djalaluddin Airport. However, in reality, the project also had an unfavorable impact on the farming community around the road infrastructure development area. This reality is the background for writing this scientific paper with the formulation of the problem of how the socio-economic impact of the construction of the Gorontalo Outer Ring Road (GORR) has been for farming communities in Talulobuto Selatan Village, Tapa District, Bone Bolango Regency which is the location for the GORR construction.